Tailored management of cavernous malformations in women: considerations and strategies—a review - Delal Bektas; Delal Bektas; Giuseppe Lanzino; Kelsey M. Smith; Kelly D. Flemming (Frontiers in Neurology)
Purpose of reviewCavernous malformations (CM) are vascular lesions in the brain and spinal cord, characterized by clusters of endothelial-lined caverns lacking proper tight junctions. These malformations may be discovered incidentally or present with symptoms such as headaches, focal neurologic deficits, or seizures, with or without hemorrhage. This review focuses on non-surgical management considerations important for women with CM, who face challenges related to pregnancy, exogenous hormone use, anticonvulsive therapy, bone health, and mental health.Recent findingsEmerging evidence suggests that both estrogen and progesterone may influence CM lesion behavior. Exogenous hormones, including those in oral contraceptives and oral hormone replacement therapy, indicate an elevated risk of symptomatic hemorrhage (SH) and may also influence seizure frequency and severity, particularly in women taking antiseizure medications (ASMs). Data suggest that the risk of CM hemorrhage during pregnancy is similar to the risk when not pregnant, although limitations to these studies will be reviewed.SummaryThis review synthesizes the current literature on the interplay between estrogen and progesterone and CM lesion behavior, highlighting the importance of gender- and sex-specific factors in clinical decision-making. Special attention is given to the implications of exogenous hormone use, seizure management, and the psychological well-being of women with CM, underscoring the need for a multidisciplinary approach tailored to the unique needs of this patient population.